Heterogeneity correction in the construction of optimized planning in radiotherapy using linear programming - Viana, Rodrigo Sartorelo Salemi; Florentino, Helenice de Oliveira [UNESP]; Lima, Ernesto Augusto Bueno da Fonseca; Fonseca, Paulo Roberto da; Homem, Thiago Pedro Donadon (Sociedade Brasileira de Pesquisa Operacional, 2011)
A radiotherapy planning is considered optimal when all the parameters involved, physical or biological, have been investigated and appropriate for each patient. In this type of planning, the major concern is with the tumor irradiation with the minimum possible damage to healthy tissues of the irradiated region, especially the organs at risk. The optimal planning for radiotherapy can be aided by Linear Programming and there is a wide literature addressing this subject. However, most published mathematical formulations do not contemplate a scenario in terms of practical applications, because they do not incorporate the heterogeneous composition of the irradiated tissue. This paper presents a methodology for heterogeneity correction in the composition of different types of irradiated tissues based on proportions among their different linear attenuation coefficient.
Keywords: linear programming; optimization; radiotherapy